C-Reactive Protein in Idiopathic Inflammatory Myopathies. Issue 1 (3rd April 2015) - Hanisch, Frank; Zierz, Stephan
Abstract: Objectives : To characterize C-reactive protein [CRP] in polymyositis [PM], dermatomyositis [DM], Jo-1 syndrome [Jo-1] and sporadic inclusion body myositis [sIBM]. Methods : C-reactive protein obtained before the start of immunosuppressive therapy was analyzed retrospectively in 61 therapy naïve patients [PM n  = 27, DM n  = 15, Jo-1 n  = 5, sIBM n  = 14]. All patients had a diagnosis of idiopathic inflammatory myopathy confirmed by muscle biopsy. Results : C-reactive protein was significantly higher in DM and Jo-1 compared to PM and sIBM [ANOVA p  < 0.001]. The CRP levels less than twice the upper limit were found in 79% of sIBM patients, 85% of PM patients, 20% Jo-1 of patients, 53% of DM patients. C-reactive protein showed no correlation with creatine kinase and erythrocyte sedimentation rate. Conclusions : The CRP is elevated in a minority of patients with myositis, mostly associated with interstitial lung disease and malignancies.